Epidemiological surveillance on syphilis in the pregnancy at centro de saúde do Uruará-Área Verde district - Pires, Osmarina N; Pimentel, Zilma NS; Santos, Marcos Vinicius S; Santos, Wilkcy A (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Introduction: syphilis is the cause of great morbidity in the intrauterine life, with disastrous effect for the embryo and negatives for gestation, representing a problem of public health in the maternal-infantile, a priority group for the Ministry of Health politics. Objective: to evaluate epidemiological surveillance on syphilis in the pregnancy, a cross sectional study was conducted from 143 handbooks of pregnant women supported by prenatal service in the period of February 1st to May 31st 2007, in the community of Centro de Saúde do Uruará - Área Verde district, Santarem, Pará, Brazil. Methods: the effectiveness of the surveillance was related with the one indicated by the Ministry of Health, referring to non-treponemic test (VDRL) request according to maternal age of adhesion to the program, numbers of previous childbirths and abortions. Results: from the considered samples: maternal age extension ranged from 14 to 37 years-olds, there were 56 pregnant women under 20 years-old; 23 (16,1%) with clinical histories of previous abortions; 114 (79,7%) enrolled the prenatal service from the 13th week of pregnancy; treponemic test was requested to 140 women (97,9%) but for one was not asked to do any test. Conclusions: the data of this study show the possibility of evaluating syphilis surveillance in pregnancy from serological tests in mothers (as well as prenatal service) as an effective indicative signal of the problem, guiding health surveillance practices as an attempt to control and eliminate congenital syphilis in the community analyzed and also in the city.